(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the effectiveness of modern teaching methods in a digital learning environment. The impact of digital technologies, interactive teaching methods, and innovative pedagogical approaches on the quality of education is studied. In the course of the research, questionnaires were conducted among teachers and students, and the results were analyzed using statistical methods. Based on the research results, recommendations were developed for a more effective organization of the digital learning process